Heavy decline of the largest European Arctic Skua Stercorarius parasiticus colony: interacting effects of food shortage and predation. Issue 1 (2nd January 2021) - van Bemmelen, Rob S.A.; Schekkerman, Hans; Hin, Vincent; Pot, Morrison T.; Janssen, Kirstin; Ganter, Barbara; Rösner, Hans-Ulrich; Tulp, Ingrid
ABSTRACT: Capsule: The number of breeding pairs of Europe's largest Arctic Skua Stercorarius parasiticus colony at Slettnes, Norway, showed a dramatic decline of at least 50% over two decades, with food shortage in four years and increasing predation by Red Fox Vulpes vulpes leading to total breeding failure in five out of six recent study years. Aims: To document the decline of Europe's largest Arctic Skua colony and quantify bottom-up and top-down effects on reproduction. Methods: We compared nest counts between 1997–1998 and 2014–2019 and collected data on egg size, clutch size and nest success for all years, and adult body mass, nest attendance, at-sea activity, aggressive nest defence, Red Fox Vulpes vulpes encounters, daily nest survival and adult survival for 2014–2019. We deployed nest cameras to identify predators in 2018–2019. In addition, we developed a demographic model to estimate the fecundity required for a stable population. Results: A higher proportion of time spent at sea, small eggs, low adult female body mass and indirect assessment of foraging fish availability suggested food shortages in four of six recent study years. At the same time, nest predation by Red Foxes, the likely predator involved, increased during the six-year study. The combined effects of food shortage and nest predation led to total breeding failures in 2017–2019. Conclusion: We provide evidence of both bottom-up (food shortage) and top-down (predation) effects on reproductive investment and hatching success in this colony. The reproductive output in recent years is far too low to sustain a stable population. The severe decline of the Arctic Skua colony at Slettnes fits reported trends for this species across most of its European breeding range, as well as for its important host species, the Arctic Tern Sterna paradisaea and the Black-legged Kittiwake Rissa tridactyla .